Perancangan Interior Restoran Bakery Jepang di Surabaya - Rendra Soenaryo; I Gusti Ngurah Ardana; Diana Thamrin (Intra, 2017)
The development of restaurants in Surabaya continues to increase from year to year. But some restaurants have failed in the business due to lack of strong identity of a restaurant. Thus there is still an opportunity to provide a place to eat, with a special feature of the Japanese bakery restaurant. The design method used is the design thinking method proposed by Linda Naiman with the adjustment. The design stage is discover, reframe, incubate, ideate, evaluate, prototype, deliver, iterate. The design that has been done with the purpose of having a specific identity, is achieved by implementing the concept of Captivating Experience in Japanese Culture. Several concept implementations in the design decisions are as follows: providing a Bakery facility that allows consumers to shop for snack-related items on the 1st floor, a luxury-dining public area and a Japanese-style sushi bar as well as a VIP room that provides a teppan experience to its users on 2nd floor, common dining area to increase the number of consumers and tatami dining areas suitable for consumers who want to relax enjoy tea like Japanese culture on the 3rd floor.